Positive Meaning: The Typical Coping of Resilient Person Towards Changing Conditions Become Individual with Disability - Wiwin Hendriani (The Center for Disability Studies and Services Brawijaya University, 2018)
Previous research (Hendriani, Retnowati, and Koesbardiati, 2011) has found that coping is the mechanism that determines adaptation and attainment of individual resilience in changing conditions become persons with disabilities. Among the active coping sequences identified, the individual's positive meaning of crithical events raises a motivational effect and reinforces the individual to be able to adapt to new life as a person with a disability. This study aimed to follow up the findings by exploring deeper positive meaning of participants who meet resilient criteria. A qualitative phenomenological approach was used to achieve that goal. The study participants were four of eight individuals with disability that also participated in the previous research (Hendriani, Retnowati, dan Koesbardiati, 2011). Researchers used in-depth interviews to extract data, and analyzed them with interpretive phenomenological analysis techniques. The results showed that each participant has a typical positive meaning to the event that made them experience disability. The meaning raises the other positive coping strategies that enable the individual to rise from significant psychological pressure, accept the disability and become empowered.